Manajemen Kurikulum Kuliyyatul Mu’allimin Al-Islamiyah dalam Menyiapkan Guru yang Berkualitas: Kuliyyatul Mu'allimin Al-Islamiyah Curriculum Management in Preparing Quality Teachers - Rifa'i, Feri Lukman; Ali, Mohammad; Musthofa, Triono Ali; Al Mubarok, Fahmi Ulum (STAI Publisistik Thawalib Jakarta, 2024)
This research aims to analyze curriculum management at Kulliyatul Mu'allimin Al Islamiyah in preparing quality teachers. The research method is qualitative, with data collection techniques including interviews, observations, and documentation. The results show that at the planning stage, the curriculum is designed based on the needs of Islamic education and labor market demands. The curriculum implementation involves innovative and participatory teaching methods, as well as the strengthening of the religious and professional competencies of teachers. Evaluations are conducted periodically to assess the effectiveness of the curriculum and teacher performance. Curriculum development is carried out by integrating feedback from evaluations and the latest developments in education and technology. This study concludes that the structured and adaptive curriculum management at Kulliyatul Mu'allimin Al-Islamiyah plays a significant role in preparing quality teachers who possess strong religious competencies and are capable of competing in the modern education landscape.